2015
DOI: 10.1002/pbc.25442
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of overall particulate contamination exposure during multidrug IV therapy: Impact of infusion sets

Abstract: This study demonstrates that a large number of particles can be administered during parenteral multidrug infusion. The choice of drug concentration and/or the type of infusion set may reduce this. Further studies are required to evaluate adverse clinical effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
(34 reference statements)
2
26
0
Order By: Relevance
“…In this way, interactions between simultaneously infused medications are minimised. Its advantage has been demonstrated in preventing drug incompatibilities [13, 14] as well as mass flow rate disturbances both in vitro and on animals [7, 8, 14]. Our work supports its use in an HDU context and suggests a link between minimising interactions of simultaneous infused drugs and time spent in hypoglycaemia.…”
Section: Discussionsupporting
confidence: 72%
“…In this way, interactions between simultaneously infused medications are minimised. Its advantage has been demonstrated in preventing drug incompatibilities [13, 14] as well as mass flow rate disturbances both in vitro and on animals [7, 8, 14]. Our work supports its use in an HDU context and suggests a link between minimising interactions of simultaneous infused drugs and time spent in hypoglycaemia.…”
Section: Discussionsupporting
confidence: 72%
“…[50,51] Some studies indicated the advantage of using multi-lumen catheters in reducing the contact between incompatible drugs. [52,53] Perez et al studied the infusion of vancomycin hydrochloride with several incompatible drugs, using a standard and multi-lumen infusion set. The authors observed that the overall particulate contamination decreased by 68% when a multi-lumen infusion set is used instead of a standard infusion set.…”
Section: Complications Of Drug Incompatibilitiesmentioning
confidence: 99%
“…Most particles range from 1 to > 100 µm in size (even up to > 500 µm), with the majority at around 2 µm [8]. The present authors opted for a detection limit of 1 µm suggesting that particulate contamination has so far been underestimated.…”
Section: Number and Characteristicsmentioning
confidence: 99%
“…A visual examination method based on the Tyndall effect has recently been assessed [82], but the authors concluded that an evaluation of drug compatibility and parenteral nutrition could not be obtained only through the visual detection of particles. Recently, Perez et al [8] directly analysed overall particulate contamination exposure during IV therapy in children by connecting the infusion sets to a dynamic analyser system which showed that patients may receive up to millions of particles per day.…”
Section: Number and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation